Mediterranean Diet Adherence in Adolescents of Different Cultures and Geographical Proveniences: A Pilot Study - Federica Intorre; Maria Stella Foddai; Eugenia Venneria (Adolescents, 2022)
The objective of the present research was to evaluate if and to what extent the encounter between different cultures in a context of globalization may have influenced the adherence to the Mediterranean diet (MD) in adolescents. The study comprised a structured questionnaire packet that inquired about anthropometric data, demographic information and both dietary and lifestyle habits. The KIDMED questionnaire was used to evaluate the adherence to the MD. A total of 103 respondents, aged 10–24 years (39.8% born in Italy or first-generation immigrants from Mediterranean countries) were included in the study. The results showed the highest percentage of adolescents having a medium adherence to the MD (44.7%), without differences according to geographical area of origin. Furthermore, the study proved that a higher adherence to the MD was significantly associated with daily breakfast (p = 0.008) and the consumption of fruit and vegetables (p = 0.002 and p = 0.000, respectively). Volunteers representing some of the different cultures and geographical proveniences currently present in Italy were perfectly integrated regarding diet and lifestyle, aspects considered in this study. Our investigation suggests the existence of incorrect dietary habits. It is certainly necessary to implement public health policies targeting adolescents to promote healthier lifestyle choices; the nutritional patterns of the MD should be among these choices.